A New Interpretation of the‘To Be or Not to Be’Soliloquy in Hamlet by William Shakespeare - Zhao, Xuefei (Pacific International Journal, 2022)
In Hamlet written by William Shakespeare, there are seven soliloquies uttered by the Hamlet. Most of the soliloquy exists as a paradox: Hamlet is questioning life and death, being and not being. In this paper, the emphasis will be on the most famous ‘To Be or Not to Be’ soliloquy interpreted by Hamlet. This paper gives a new interpretation of the ‘To Be or Not to Be’ soliloquy analyzed from a discourse perspective and a psycholinguistic perspective to demonstrate how it helps to forward the plot to achieve the dramatic effectiveness and to make different characters more distinctive. With this object, the position and the significance of the soliloquy ‘To Be or Not To Be’ in Hamlet is going to be concluded.